2000
DOI: 10.1111/j.1532-5415.2000.tb02638.x
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity and Comorbidity in Relation to Functional Status: A Community‐Based Study of the Oldest Old (90+ Years)

Abstract: OBJECTIVES: To describe health and functional status in the oldest old; to explore the relationships of morbidity and functional status; and to verify whether this relationship was modified by gender. DESIGN AND SETTING: A community-based survey including all inhabitants aged 2 9 0 living in central Stockholm, Sweden. All participants were clinically examined by physicians, cognitively assessed by psychologists, and interviewed by nurses. Diagnoses were made according to the International Classification of Dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
35
1
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 36 publications
7
35
1
2
Order By: Relevance
“…It is also reported that in spite of their advanced age, a great proportion of nonagenarians are functionally independent [25]. In agreement with the existing literature, we found that the functional status of more than 50% of our patients was rather well preserved.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…It is also reported that in spite of their advanced age, a great proportion of nonagenarians are functionally independent [25]. In agreement with the existing literature, we found that the functional status of more than 50% of our patients was rather well preserved.…”
Section: Discussionsupporting
confidence: 81%
“…Previous data from studies about the very old have shown that the majority of them are women, usually widowed, and living at home [25]. It is also reported that in spite of their advanced age, a great proportion of nonagenarians are functionally independent [25].…”
Section: Discussionmentioning
confidence: 99%
“…One surprising finding was the absence of a statistically significant association between gender and functional capacity, differently from other studies in which functional incapacity was associated with the female gender (4)(5)(6)(16)(17) . No association was found for the marital status variable either when included in the logistic regression model.…”
Section: Discussioncontrasting
confidence: 53%
“…The Vantaa 85+ Study [31] recruited all people at least 85 years of age living in the city of Vantaa, Finland. Two Swedish studies have used a similar approach to recruiting: one recruited all 95+ year olds registered in the city of Göteborg [48], the other recruited all 90+ year old inhabitants of the Kungsholmen district [49]. As we can see, these studies have selected different methods for investigating extreme aging.…”
Section: Investigations In the Oldest-oldmentioning
confidence: 99%